Cuaderno de trabajo y guía didáctica para la asignatura de educación para la ciudadanía, orientado a docentes y estudiantes del tercer año de bachillerato del colegio “Daniel Córdova toral” de la ciudad de cuenca, año lectivo 2014 - 2015 - Guerrero Guerrero, Luis Oswaldo (2015)
The Intercultural Education Act stipulates that the State have a duty inescapable and essential to ensure the right to education, the inhabitants of Ecuadorian territory and its universal access throughout life, which will generate the conditions that ensure equal opportunities to enter remain, mobilize and graduate from educational services. The State exercises the rectory on the education system through the national education authority in accordance with the Constitution and the law, and which will guarantee a quality public education. It also recognizes that the State through the Ministry of education, will provide the respective equipment at public educational institutions, as well as the continuous improvement of the quality of education The Ministry of education will ensure all educational institutions to develop a comprehensive education, with a transversal vision and focusing to rights, also ensuring the mandatory application of a national curriculum, both in the public, municipal and private institutions and charters at its various levels: initial, basic and secondary education. The provisions identified in the law of Intercultural education gives this authority to the highest authority in the field, available which largely meets it, however there are some subjects as for example the education for the citizenship that is taught in the third year of high school, to date it does not count with a tutorial to make the Professor of this subject can carry out the teaching of it in the best way. This situation warns an imperative need in order to develop an educational guide and a workbook so people or teachers of this subject may have the necessary elements to achieve efficiency in the process of teaching - learning. With this background and an evident empty in ministerial settings, born this thesis previous to the obtaining of the title of Bachelor in Sciences of Education, educational computing mention, in which the main axis is after deeply address the issue, file a didactic guide for the subject of education for the citizenship for the third year of secondary school education Daniel Cordova Toral of Cuenca city and why not for the rest of institutions whether public education, municipal, private or charters, which will undoubtedly guarantee the best performance in educational work.